Tithonia diversifolia (Hemsl.) A. Gray: Botany, Bioactivity, and Secondary Metabolites - Marina Silalahi (Pro-Life, 2026)
Tithonia diversifolia is widely found across various landscapes in Indonesia, from roadsides and neglected areas, and information on its use remains limited. This study aims to explain the botany, bioactivity, and secondary metabolites of T. diversifolia. This research is based on a review of online literature using the keywords T. diversifolia, uses T. diversifolia, and secondary metabolites of T. diversifolia. Tithonia diversifolia is a perennial shrub-like plant, growing to 1.2 – 3 m, easily recognized by its cup-shaped yellow ribbon flowers. The bioactivities of T. diversifolia include antimicrobial, antioxidant, anti-inflammatory, anticancer, antidiabetic, and Alzheimer's disease treatment. Various researchers have reported that T. diversifolia inhibits the growth of Pseudomonas aeruginosa, Staphylococcus aureus, Escherichia coli, Bacillus subtilis, Proteus mirabilis, Salmonella typhi, Shigella dysenteriae, Corynebacterium diptheriae, Streptococcus pneumoniae, Saccharomyces cerevisiae, Microbacterium foliorum, and Rhodococcus equi. Epicatechin and quercetin are promising antibacterial agents. The bioactivity of T. diversifolia as a microbial agent is more pronounced than that of other species, making it highly promising for development as an alternative antibiotic.